Shortened sleep fuels inflammatory responses to marital conflict: Emotion regulation matters. (May 2017) - Wilson, Stephanie J.; Jaremka, Lisa M.; Fagundes, Christopher P.; Andridge, Rebecca; Peng, Juan; Malarkey, William B.; Habash, Diane; Belury, Martha A.; Kiecolt-Glaser, Janice K.
Highlights: Couples' shorter sleep duration related to higher stimulated cytokine production after marital conflict. People who slept less behaved more negatively and less positively only when their partner had also slept less. One's own and one's partner's use of emotion regulation strategies during conflict buffered short-sleep-related inflammatory reactivity. Abstract: Sleep problems can boost inflammation and may jeopardize interpersonal functioning, risks that may be magnified in couples. This observational study examined the effects of self-reported recent sleep duration on couples' inflammation, inflammatory responses to a problem discussion, interpersonal behavior, and use of emotion regulation strategies (emotion expression, cognitive reappraisal) during conflict. People who slept less had higher stimulated interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) production after the marital problem discussion than those who slept more. However, using emotion expression and cognitive reappraisal strategies during conflict protected couples who slept less from inflammatory reactivity. Specifically, people's short sleep did not relate to inflammatory increases when they expressed their own feelings more or when their partner reappraised or expressed their emotions more. When both partners slept less, couples interacted in a more hostile way than when at least one partner slept more. These data point to the combination of short sleep and marital conflict as a novel path to heightened inflammation, a risk that partners' emotion regulation strategies may counteract. The study also highlights the role of short sleep in more negative or punishing marital behavior.